Compact UWB bandpass filter with dual‐notch bands using asymmetric tri‐section stepped impedance resonator. Issue 6 (30th March 2018) - Kumari, Puja; Pal, Manimala; Sarkar, Pankaj; Ghatak, Rowdra
Abstract: In this study, a novel high selective UWB band pass filter (BPF) with dual notch band is presented. UWB BPF is realized using stub‐loaded multiple‐mode resonator (MMR). The MMR is constructed by loading a quintuple mode open stub at the centre in an asymmetric tri‐section stepped impedance resonator (ATSSIR). Five modes, including two odd modes and three even modes, placed within UWB band. Two transmission zeros generated by the fractal stub improve the passband selectivity greatly. Two half wavelength long fractal Hilbert resonators are embedded near I/O line to achieve notch bands at 5.1 and 5.9 GHz. Aperture‐backed interdigital coupled‐lines are implemented to improve the coupling. The proposed prototype is fabricated and tested. The measured insertion loss is observed to be within 1.5 dB over the passband. By virtue of two transmission zeros (TZs), on either side of the passband, at 5.1 and 5.9 GHz, respectively, the passband selectivity is achieved with measured roll‐off factor at around 34 dB/octave. The out‐of‐band rejection of the filter is greater than 22 dB up to 18 GHz. The simulated results are in good agreement with the measured responses.